Pengaruh Perkembangan Kognitif Anak Usia 5-6 Tahun Terhadap Kesiapan Sekolah Dasar - Oktarina Dwi Handayani; Annisa Namira Rinaldi (Jurnal Ilmiah POTENSIA, 2024)
This study aims to measure the influence of cognitive development on school readiness in children aged 5-6 years. The sample for this research was children who sat in kindergarten at height B in the Tanjung Priok area, North Jakarta. Based on the results of research conducted at 18 PAUD institutions by taking data from 152 students. This research was conducted using a quantitative correlational method using Spearman's rank correlation coefficient to determine the influence of the variables cognitive development (Y) and school readiness (x). Cognitive development has a positive effect on the development of school readiness. The contribution of the results of this research can be used as a reading source and reference for teachers, parents and the community in providing stimulation for elementary school readiness so that it has a positive impact on academic achievement.